Scans and Convolutions-A Calculational Proof of Moessner's Theorem - Hinze, R (2011)
The paper introduces two corecursion schemes for stream-generating functions, scans and convolutions, and discusses their properties. As an application of the framework, a calculational proof of Paasche's generalisation of Moessner's intriguing theorem is presented. © 2011 Springer-Verlag.